Stages of collective identification of a freedom-fighter narratives of three Mujahedeen. [article]. - Inzon, Charlie M.
This study examined stages of behavioral involvement and identity themes associated with the development of collective identification with a liberation movement. The research interviewed three former Moro Islamic Liberation Front (MILF) members in Maguindanao. The researchers used the life story method to gather and analyze data. Findings showed five stages in the making of Mojahedeen: entry, engagement, assessment, disengagement-reintegration, and starting new involvement. Discussion focused on the role of social context and situation in behavioral and cognitive stages associated with collective identification, the appropriateness of life-story method in collective identification research, and implication to Mindanao problem. -- (from the author)